Diagnostic accuracy of diffusion restriction in intraductal papillary mucinous neoplasm of the pancreas in comparison with "high-risk stigmata" of the 2012 international consensus guidelines for prediction of the malignancy and invasiveness. (October 2017) - Kim, Mimi; Mi Jang, Kyung; Kim, Seong Hyun; Doo Song, Kyoung; Jeong, Woo Kyoung; Kang, Tae Wook; Kim, Young Kon; Cha, Dong Ik; Kim, Kyunga; Yoo, Heejin
Background: It is debated whether diagnostic performance of diffusion-weighted imaging (DWI), which is widely used for detection and characterization of various malignant tumors, is comparable with high-risk stigmata of 2012 international consensus guidelines (ICG) for diagnosis of intraductal papillary mucinous neoplasms (IPMNs). Purpose: To evaluate the diagnostic accuracy of diffusion restriction in IPMNs for prediction of malignancy and invasiveness in comparison with high-risk stigmata of 2012 ICG. Material and Methods: This retrospective study was institutional review board approved and informed consent was waived. A total of 132 patients with surgically proven IPMNs (49 malignant, 83 benign) who underwent gadoxetic acid-enhanced magnetic resonance imaging (MRI), magnetic resonance cholangiopancreatography (MRCP), and DWI with a b -value of 0, 100, and 800 s/mm 2 using a 3.0 T MR system were included. Two radiologists independently evaluated imaging parameters of high-risk stigmata and worrisome features of 2012 ICG and diffusion restriction in IPMNs. Univariate and multivariate logistic regression analyses and McNemar's test were used for statistical analysis. Results: The presence of diffusion restriction in IPMNs was the only independent imaging parameter for prediction of malignancy (odds ratio [OR], 11.98; 95% confidence interval [CI], 3.60–39.87; P  < 0.001) and invasiveness (OR, 17.92; 95% CI, 3.91–82.03; P  < 0.001) on multivariate analysis. The diagnostic accuracy and specificity of diffusion restriction were significantly improved compared to high-risk stigmata of 2012 ICG to prediction of malignant ( P =  0.006 and P <  0.001, respectively) or invasive IPMNs ( P =  0.009 and P =  0.015, respectively). Conclusion: The diffusion restriction in IPMNs could be considered as another high-risk stigma of malignancy and predictor for invasiveness.